KNYGA – ŽAVINGOJI SENA DAMA - MACEVIČIŪTĖ, ELENA MACEVIČIŪTĖ (Knygotyra, 2015)
Vilniaus universiteto Knygotyros ir dokumentotyros institutasUniversiteto g. 3, LT-01513 Vilnius, LietuvaEl. paštas: elena.maceviciute@kf.vu.lt